Development and validation of a multidimensional questionnaire for evaluating quality of life in melasma (HRQ-melasma) - Pollo, Camila Fernandes [UNESP]; Miot, Luciane Donida Bartoli [UNESP]; Meneguin, Silmara [UNESP]; Miot, Hélio Amante [UNESP] (FapUNIFESP (SciELO), 2018)
Background: Melasma has a major impact on quality of life. MELASQoL is the only validated specific psychometric instrument to evaluate melasma QoL. Objective: To develop and validate a multidimensional questionnaire for evaluating quality of life related to facial melasma. Methods: Cross-sectional study performed in 2 institutions (public and private) from Brazil. Two focus groups were carried out: 5 board-certified dermatologists and 10 melasma patients, indicating the dimensions and significant units of melasma QoL. The preliminary questionnaire with 49 itens was applied to 154 facial melasma patients. Item reduction was performed by Rasch analysis. Parallel evaluations of clinical (MASI), demographic, and QoL aspects (MELASQoL, DLQI) were performed. The dimensional structure was assessed by confirmatory factor analysis. Temporal stability was tested in a subgroup of 42 individuals within 7-14 days. Results: The mean (SD) age of the 154 interviewed subjects was 39±8 years, and 87% were females. The median (p25-p75) DLQI and MELASQoL were: 2 (1-6) and 30 (17-44). HRQ-Melasma consisted of 19 items distributed in 4 dimensions: Physical/Appearance, Social/Professional, Psychological, and Treatment. Cronbach’s alpha for HRQ-Melasma was 0.96, and >0.74 for each dimension. There was high correlation between HRQ-Melasma and DLQI and MELASQoL (rho=0.80 and 0.83), but modest with MASI (rho=0.35). Dimensional structure of HRQ-Melasma was stated by confirmatory factor analysis coefficients. Test-retest analysis disclosed an intraclass correlation coefficient of 0.91 (p<0.01). Study limitations: Single-center study. Conclusions: A specific instrument to evaluate QoL in melasma with multidimensional characteristics was developed and validated, with appropriate psychometric performance.
Keywords: Melanosis; Psychometrics; Quality of life